Preference in learning gross anatomy among IIUM students - Aung, Htar Htar; Tin, Myo Han; Tin, Moe Nwe (Malaysian Anatomical Conference, 2011)
Both medical (Year I, Year II) and dental (Year I) students in IIUM are exposed to three types of teaching aids in learning gross anatomy. They are cadavers, prosected wet specimens and plastic models. This study aimed at exploring the students’ preference on teaching aids in learning gross anatomy and reasons for their preference. A cross-sectional comparative study was carried out among 185 medical and dental students by using the pretested, semi structured, self administrated questionnaires including open-ended questions. Significance of preferences were analysed by X2 test. Year I (99%) and Year II (97%) medical students preferred the plastic models as the best approach to learn gross anatomy because of their handleability and portability. Year I dental students (96%) preferred the prosected wet specimens because they were real human structures and well preserved. The preferred and less preferred rates were 86% and 4% for plastic model, 84% and 10% for prosected wet specimen and 77% and 17% for cadaver. These differences were statistically significant (p <0.05). Students didn’t prefer the cadavers most but they agreed that the cadavers are more realistic, informative and easier to remember. This study indicates that students prefer all three types of teaching aids while the most preferred one is the plastic model. The quality of teaching aid is the reason for their preference. Students’ suggestion to use the advanced technologies such as three dimensional animations or simulated videos should be considered to get discernable learning outcomes.